Estudo de comunidades de foraminíferos em manguezal do Rio Itapanhaú, Bertioga-SP, aplicado à reconstrução paleoambiental - Angelis, Gabriela Matsunaga de [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Foraminifera scientific studies became, historically, of your apply in relative dating of rocks, stratigraphic correlations and paleoenvironmental reconstruction. In the last decades, they have been applied on the studies of modern ecosystems, with or without antrhopic influence. Both aspects are interest of petroleum industry. Among other approaches, foraminífera are used as good indicators of the fluctuation of relative sea level. This study aimed to survey and taxonomic study of the community structure of foraminifera in surface samples of a core, 60 cm, collected in mangrove located in Itapanhaú river in Bertioga (SP).It also aims to contribute to the discussion about typical patterns of community structure of mangrove margins and provide elements for discussion on the relative sea level behavior in this area in almost modern times. It was been collected 6 samples along the core of 60 cm of length, each one 10 cm depth. They were made in laboratory and in each sample sought to find at least 100 foraminifera per ml. The species identification was made with reference specified material and collection available on IGCE-UNESPetro, Rio Claro. The community structure was studied in terms of richness, diversity and species composition and was made the results comparison from similar areas to interpret the depositional environment. Were found 21 species within them 13 calcareous and 8 binders, being the most abundant and frequent species Ammonia tepida, Ammonia parkinsoniana e Elphidium spp. Essentially there wasn’t change in the community structure within the period covered by the core which reflects an environment of outer margin of mangrove without noticeable change in relative sea level at the respective time of deposition of muddy sediments. The community structure here recognized its similar to estuarine environment well maintained which indicates a low human impact in the area over the time interval. The agreement of the results...

Estudos científicos sobre foraminíferos decorrem, historicamente, de sua aplicação para datação relativa de rochas, correlações estratigráficas e reconstruções paleoambientais. Nas últimas décadas, vêm sendo amplamente aplicados aos estudos de ecossistemas modernos, com ou sem influência antrópica. Ambos os aspectos interessam à indústria do petróleo. Dentre outros enfoques, os foraminíferos são usados como bons indicadores de flutuação do nível relativo do mar. O presente estudo teve por objetivo realizar o levantamento taxonômico e o estudo da estrutura de comunidades de foraminíferos em amostras de um testemunho superficial, de 60 cm, coletado em manguezal localizado no Rio Itapanhaú, em Bertioga (SP). Objetiva ainda contribuir para a discussão sobre padrões típicos da estrutura de comunidades em margens de manguezal e oferecer elementos para discussões sobre o comportamento do nível relativo do mar nesta área em tempos quase modernos. Foram coletadas 6 amostras ao longo de um testemunho de 60 cm de comprimento, uma a cada 10 cm de profundidade. Estas foram preparadas em laboratório e em cada amostra buscou-se encontrar ao menos 100 tecas por 1 ml. A identificação das espécies foi feita com material de referência específico e coleção disponível no IGCE-UNESPetro, Rio Claro. A estrutura das comunidades foi estudada em termos de riqueza, diversidade e composição das espécies, sendo feita uma comparação dos resultados obtidos com os de áreas similares para interpretação do ambiente deposicional. Foram encontradas 21 espécies, dentre elas 13 calcárias e 8 aglutinantes, sendo Ammonia tepida, Ammonia parkinsoniana e Elphidium spp. as espécies mais abundantes e frequentes. Essencialmente, não houve alteração da estrutura das comunidades ao longo do intervalo coberto pelo testemunho, o qual reflete um ambiente de margem externa de manguezal sem alteração perceptível do nível relativo do mar...
Keywords: Ecologia aquatica; Foraminifero; Manguezais; Paleoambiente; Itapanhaú, Rio (SP); Bertioga (SP)